Determination of Combustible Properties of Palm Kernel Shell and Palm Fiber Mixture for Heat Generation - O. H, Salaudeen; J. O, Awulu; E, Deraor (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
This research investigates the potential of palm kernel shell (PKS) and palm mesocarp fiber (PMF) as alternative energy sources for rural community. Using a Bomb Calorimeter, the calorific values of agricultural waste materials in both raw and briq form. The results reveal that briquet forms have higher calorific values, with palm kernel shell at 27.35MJ/kg and palm mesocarp fiber briquettes at 25.92MJ/kg, compared to their raw counterparts at 24.04MJ/kg and 22.97MJ/kg, respectively. Based on the results of physical properties like moisture, ash, and volatile matter content. Majority of the parameters meet the minimum standard for calorific value (10MJ/kg – 35MJ/kg), indicating that these materials are viable for energy production. Palm kernel shell shows superior qualities, with a higher mass (25.5g) compared to palm mesocarp fiber (5.08g), and better FBR and SFC values. By using these agricultural wastes as energy sources, the dependency on fuel wood can be reduced, thereby mitigating deforestation, soil degradation, and the impacts of climate change.